Predicting customers’ adoption of Islamic banking services in Tunisia:A Decomposed Theory of Planned Behaviour approach - Abdelghani Echchabi; Dhekra Azouzi (Institute for Research and Community Empowerment (LPPM TAZKIA), 2015)
Objective -The main purpose of the study is to examine the willingness of the Tunisian customers to adopt Islamic banking services, and the factors that may influence their decision.Methods - A total of 100 questionnaires were randomly distributed to Tunisian banking customers, out of which 93 were properly filled and returned. Multiple regression and one sample t-test were subsequently applied.Results – The results showed that uncertainty, compatibility, awareness as well as subjective norm, have a significant impact on the attitude towards Islamic banking services in Tunisia. Likewise, normative belief was also found to have a significant influence on subjective norm, with particular reference to the parents, siblings, peers and colleagues, as the main referent groups. In addition, self-efficacy was found to have a significant influence on perceived behavioural control, and finally, attitude and subjective norm were found to have a significant impact on the intention to adopt Islamic banking services in Tunisia.Conclusions -Tunisian customers are willing to shift to Islamic banking services. Keywords: Tunisia, Islamic Bank, Decomposed theory of planned behaviour